TREN TRANSFORMASI BISNIS: DAMPAK INOVASI PRODUK DAN DIGITAL MARKETING PADA REPURCHASE INTENTION MELALUI BRAND IMAGE - I Gusti Ayu Imbayani; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
In a fiercely competitive business era, a company's success is not only determined by the products or services it offers, but also by its ability to truly understand and fulfil customers' needs and wants through its products and digital marketing. By understanding customers deeply, companies can design effective marketing strategies that focus on creating sustainable satisfaction for customers, so as to make customers loyal and willing to buy products again. This study aims to analyse the role of brand image in mediating the effect of product innovation and digital marketing on repurchase intention. The sampling technique used in this study is a non-probability sampling technique, namely purposive sampling. The data analysis technique used in this research is partial least square (PLS). The results showed that product innovation and digital marketing have a positive and significant effect on repurchase intention and brand image is able to mediate product innovation and digital marketing on repurchase intention. In an effort to increase repurchases, companies must focus on developing product innovation and digital marketing strategies..